Dampak harga diri, kepuasan hidup, dan depresi terhadap kesejahteraan psikologis mahasiswa keperawatan Poltekkes Kemenkes Aceh - Eka Warnidar; Arif Rahman Aceh; Ritawati Ritawati; Saiful Oetama (Poltekkes Kemenkes Aceh, 2024)
Background: Psychological well-being is a very important component in the training and development of nursing students, because it can increase productivity and success in the academic and training activities they undergo. If this psychological well-being problem is not resolved, it will affect students' social interaction, achievement and interest in learning and this will have a negative impact on the future process.Objectives: This study aims to analyze the factors related to the psychological well-being of nursing.Methods: This research has an analytical survey design with a correlational approach. The number of samples in this study was 642 respondents. The sampling technique in this research is total sampling. The research was conducted at a health polytechnic in Aceh in 2020. Data was collected using the Psychological Well-Being Scale questionnaire, Rosenberg Self Esteem Scale, Satisfaction With Life Scale via Google form and using Mann Whitney U Test analysis.Results: The results of the stepwise analysis show all independent variables, namely difficulties in social relations (p= 0.01), self-esteem (p= 0.01), depression (p= 0,01) and life satisfaction (p= 0,02) are the dominant predictors related to psychological well-being in Diploma III Nursing students. Conclusion: This research recommends planning interventions for nursing students to improve their psychological well-being, taking into account these dominant factors.